Analysis of the influence of road infrastructure on the economic growth of the Mama district in the period 2003-2013 - Laen Sugi Rante Tandung Tandung (Indonesia Accounting Research Journal, 2022)
The purpose of this research aims to analyze the effect of road infrastructure's expenditure, and the road quality toward the Growth of Economy of Mamasa Regency by using secondary data in the form of time series for the period 2003-2013. The analysis method used in this research was 2SLS .This research uses economic growth and condition of the road as the dependent variable while the independent variable is the government expenditure on road infrastructure.As the result, the effect of the road infrastructure toward economic growth showed that the government expenditure has been positive but insignificant correlation toward economic growth while the decreasing correlation of the road quality gives insignificant correlation toward economic growth.